The 4th 2011 Biomedical Engineering International Conference 2012
DOI: 10.1109/bmeicon.2012.6172028
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of open slot angle for asymmetry slot antenna using 3D finite element method

Abstract: This paper presents analysis of asymmetry slot antenna configuration for microwave ablation at 2450 MHz using three-dimensional finite element analyses treatment for liver tissue. We designed new coaxial-slot antenna is opened slot at one-side of antenna. We study heat transfer for liver tissue by used MW Ablation system, varying the angle of open slot at 90°, 180°, 270° and 360°. The results illustrate that the coaxial-slot asymmetry structure antenna can be used in microwave ablation for treatment of the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In Fig. 14., it is observed that the temperature distribution of the proposed MOFDM for OASPS is in the more controllable shape than [20], due to the sharp beam of temperature distribution to the target at the front side of slot with the less temperature distribution at the rare side of slot. The SAR results in Fig.…”
Section: Simulation Results On Mofdm For Oaspsmentioning
confidence: 96%
See 3 more Smart Citations
“…In Fig. 14., it is observed that the temperature distribution of the proposed MOFDM for OASPS is in the more controllable shape than [20], due to the sharp beam of temperature distribution to the target at the front side of slot with the less temperature distribution at the rare side of slot. The SAR results in Fig.…”
Section: Simulation Results On Mofdm For Oaspsmentioning
confidence: 96%
“…The proposed MOFDM for OASPS design output is compared to the design proposed in [20], due to the method proposed in [20] provide the comparison of open slot angle for asymmetry slot antenna using 3D finite element method with the close angle of 90, 180, 270, and 360 degrees, as shown in Figs. 14-17.…”
Section: Simulation Results On Mofdm For Oaspsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to compare the results in terms of power and application time, we have used a tissue temperature distribution model. The targeted radiation in MWA has been presented in (Thaiwat et al 2011) for slot antenna in different open angles without however discussing lesion radius in the active and non active side.…”
Section: Introductionmentioning
confidence: 99%